Penggunaan “Sketsa Gambar” sebagai Strategi dalam Menyelesaikan Soal Koinematika Gerak Lurus - Helmi Abdullah; Muhammad Arsyad; Khaeruddin Khaeruddin (Seminar Nasional LP2M UNM, 2019)
One aspect that is neglected in teaching physics is the procedure of solving physics problems. During this time, the teacher only trains students to solve the questions without giving an explanation of how to solve the problem. Even though every physics problem has its own procedure in solving it. One of the procedures that the author has developed in solving physics problems is through the use of "sketch drawings". The results showed that first year students who were taught with a sketch drawing strategy would find it easier to solve essay questions. This was indicated by an increase in scores in completing essay questions for the subject of linear motion kinematics.